2023
DOI: 10.1002/anie.202304554
|View full text |Cite
|
Sign up to set email alerts
|

CuCoO2 Nanoparticles as a Nanoprotease for Selective Proteolysis with High Efficiency at Room Temperature

Abstract: Many nanoproteases contain tetravalent metal ions and catalyze peptide‐bond hydrolysis only at high temperature (60 °C). Here, we report a new and effective strategy to explore nanoproteases from nanoparticles containing low valent metal ions. We found that flower‐like CuCoO2 nanoparticles (CuCoO2 NPs) containing low valent Cu+ possessed excellent catalytic activity towards selective cleavage of peptide bonds with hydrophobic residues in bovine serum albumin (BSA) at room temperature. CuCoO2 NPs exhibited exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Inspired by metalloproteases that contain Lewis acid metals in their active sites, various metals were combined with suitable organic ligands to form chelating complexes with a high stability and versatile reactivity that can be used for protein hydrolysis among many other biomolecular transformations. , In the past decade, our group has developed polyoxometalates (POMs) as inorganic ligands for metal cations, where the molecular recognition ability of the POM scaffolds toward protein surfaces was combined with hydrolytically active Lewis acid metal cations (Ce­(IV), Zr­(IV), or Hf­(IV)) to catalyze peptide bond hydrolysis. Despite this promising proof of concept, the relatively low reactivity of classical transition metal complexes, prompted the development of nanozymes, i.e., nanomaterials with intrinsic enzyme-like properties. The rapid evolution and growing understanding of nanomaterials allow for the engineering of active centers that mimic those of natural enzymes, resulting in nanomaterials that could address current limitations of natural enzymes. , Despite the remarkable advances in the field, most nanozymes have been designed to exhibit redox activity, mimicking the oxidase/peroxidase family of enzymes. Nanozymes that mimic other types of enzymes, such as proteases, have seen substantially less development in comparison. In this regard, metal–organic frameworks (MOFs) have recently emerged as highly reactive and recyclable catalysts for protein hydrolysis. In particular, MOFs based on Zr­(IV) and Hf­(IV) metal-oxo clusters (MOCs) have been used as catalysts for an array of different biomolecular transformations, including peptide bond hydrolysis, where theoretical studies suggested that MOCs act as the catalytically active sites. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by metalloproteases that contain Lewis acid metals in their active sites, various metals were combined with suitable organic ligands to form chelating complexes with a high stability and versatile reactivity that can be used for protein hydrolysis among many other biomolecular transformations. , In the past decade, our group has developed polyoxometalates (POMs) as inorganic ligands for metal cations, where the molecular recognition ability of the POM scaffolds toward protein surfaces was combined with hydrolytically active Lewis acid metal cations (Ce­(IV), Zr­(IV), or Hf­(IV)) to catalyze peptide bond hydrolysis. Despite this promising proof of concept, the relatively low reactivity of classical transition metal complexes, prompted the development of nanozymes, i.e., nanomaterials with intrinsic enzyme-like properties. The rapid evolution and growing understanding of nanomaterials allow for the engineering of active centers that mimic those of natural enzymes, resulting in nanomaterials that could address current limitations of natural enzymes. , Despite the remarkable advances in the field, most nanozymes have been designed to exhibit redox activity, mimicking the oxidase/peroxidase family of enzymes. Nanozymes that mimic other types of enzymes, such as proteases, have seen substantially less development in comparison. In this regard, metal–organic frameworks (MOFs) have recently emerged as highly reactive and recyclable catalysts for protein hydrolysis. In particular, MOFs based on Zr­(IV) and Hf­(IV) metal-oxo clusters (MOCs) have been used as catalysts for an array of different biomolecular transformations, including peptide bond hydrolysis, where theoretical studies suggested that MOCs act as the catalytically active sites. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Curcumin was initially loaded onto the bovine serum albumin (BSA) nanoparticles (NPs), which are commonly used natural drug carriers with low immunogenicity and good safety [17]. Due to the abundant hydrophobic structures and cavities of BSA NPs, they can effectively encapsulate curcumin and improve its solubility through hydrophobic interactions [18,19]. Then, erythrocyte membranes from septic mice were extracted and coated on the NPs to form efferocytosis-inspired nanodrug BCN@M. The damaged erythrocyte membrane increased the recognition and uptake efficiency of BCN@M by efferocytosis of macrophages.…”
Section: Introductionmentioning
confidence: 99%